Afetividade na educação em ciências : da percepção de estudantes ao discurso docente - Hahn, Tamiris de Oliveira (2018)
Starting from the assumption of the monistic education - articulation of cognitive and affective elements in the teaching and learning processes - this dissertation had as an aim to analyze the conceptions and / or the references about affectivity, present in the teachers‟ speeches from the area of Natural Sciences disciplines, and their possible reflections on their teaching practice in High School, as well as the way this relation is seen by the students. Under this perspective, the present research of qualitative nature and case-study type used as instruments of data collection: questionnaires; semi-structured interviews aimed at teachers and students; and, besides that, the observation of classes in Physics, Chemistry and Biology. The corpus selected for the analysis was examined under the light of Discursive Textual Analysis (MORAES; GALIAZZI, 2011). Thus, the individualization and categorization of the data obtained through the interviews and the observations in classroom resulted in a series of emerging categories that indicate both teachers and students recognize the importance of affective ties in the teaching and learning processes in order to qualify the pedagogical relations and, consequently, the academic results of the students. In this study, it was observed that the affective bond can be presented beneath two orders: teaching and learning and / or dialogue and social coexistence. Restricted to the commitment of teachers and students to pedagogical processes and to a more humane and sensitive education that contemplates the social, affective and cognitive dimensions of the subject, this research proposes a reinvention in the ways of teaching and learning, in order to construct an education for citizenship and not just a simple information exchange. Therefore, from the results found, it is understood that the study of affectivity and its respective applicability in the classroom seem to positively influence the development of autonomy and critical-reflexive sense of the student.